Characterization and structural modification of cold-adapted, organic solvent stable lipase from Staphylococcus epidermidis AT2 produced in Escherichia coli - Ahmad Kamarudin, Nor Hafizah (2014)
Lipase which constitutes one of the most important industrial enzymes is undeniably a versatile biocatalyst, capable of catalyzing both hydrolysis and synthesis reactions in aqueous and non-aqueous media, respectively. The search of novel lipases with unique properties is a continuous effort for decades. Locally isolated Staphylococcus epidermidis AT2 was previously identified as an organic solvent tolerant lipase producer. The mature active form of lipase gene was cloned and expressed in E. coli. Two modes of expression were investigated, intra- and extracellular expression of AT2 lipase. Intracellular expression showed an optimal specific activity of 22.16 U/mg. To improve the expression level, Bacteriocin Release Protein (BRP) system was employed using two types of BRP vectors (pJL3 and pSW1) which were distinguished by their promoter systems. The aim was to probe the effect of dependent and independent inducible promoter (between BRP vector and recombinant AT2 lipase) in mediating the extracellular expression of AT2 lipase. For both cases, an increment by 1.5-fold and 3.5-fold in the enzymatic activity compared to that of intracellular expression was detected in E. coli harbouring pJL3 and pSW1,respectively. This suggested that independent inducible promoter system permitted better regulation of BRP and AT2 lipase expression which consequently promoted higher secretion of soluble proteins into the culture medium. The enzyme was purified by two-step chromatographic method; hydrophobic interaction chromatography (HIC) and ion exchange chromatography (IEX) with 47.1% recovery and 3.5-fold purification factor. The estimated molecular weight as observed on SDS-PAGE was 43 kDa. The optimal temperature and pH were 25 °C and pH 8, respectively. The lipolytic activity was significantly enhanced by Ca2+ ions, Tween 60 and Tween 80. On the downside, EDTA, pepstatin A, Zn2+ and Fe3+ ions,showed strong inhibition on the enzymatic activity. AT2 lipase exhibited high preference towards long chain triglycerides, natural oils and was found stable in various organic solvents namely; 25% (v/v) of DMSO, methanol, ethanol, acetone,diethyl ether, toluene, and n-hexane. Following biochemical properties determination, crystallization of AT2 lipase was attempted. Crystallization screenings were conducted over purified protein at concentrations 1-5 mg/mL which resulted in several crystal hits but of low diffraction quality. To promote AT2 lipase crystallizability, large scale expression were performed and yielded a marked improvement in total purified protein thus rendering screening trials to be carried out at protein concentration of 5-10 mg/mL. Construct optimization using three fusion tags (His, GST, MBP) were prepared in which GSTHis6-tagged AT2 lipase construct was selected for purification and highthroughput crystal screenings. Yet, none of the trials yielded positive outcomes. Alternatively, AT2 lipase was subjected to structural modification to endow higher propensity of producing crystal. A homology model was built using YASARA and S. hyicus lipase as template. Aided with the knowledge on enzyme structure and crystallization prediction tools, flexible C-terminal region and surface exposed lysine were targeted for mutation. Subsequently, three mutants of AT2 lipase were constructed; M386, K214A and K325A. M386, a truncated C-terminal mutant had yielded two crystal leads. The needle-like crystals which were obtained from Formulation 46 of PEG/Ion Screen and Formulation 87 of Index Screen appeared after approximately 40 days of incubation at 10 °C albeit not suitable for structure determination. Synergistically, swapping of the tail-like region resulted in a slight shift of the thermostability profile. The lipolytic activity of M386 retained by 43% compared to its wild-type with 18% remaining activity at 45 °C. In silico analysis conducted at 25 °C and 45 °C was found to be in accordance to the experimental findings in which RMSD values of M386 was more stable and less fluctuated throughout the total trajectory in comparison to its wild-type. Terminal moieties were also observed to exhibit large movement and flexibility as denoted by high RMSF values at both dynamics. Variation in organic solvent stability property was also detected where lipolytic activity of M386 was stimulated in the presence of 25% (v/v) of DMSO, isopropanol and diethyl ether. Surface lysine mutants, K214A and K325A, on the other hand, could not be crystallized. Single mutation by substitution of high entropy residue, lysine to alanine on high entropy patches did not likely to engage any intermolecular crystal contacts required for crystal packing. However, changes in organic solvent stability profile were observed. Both K214A and K325A displayed activation of lipolytic activity in polar organic solvents. Enhancement of lipolytic activity in K214A was detected in ethanol, acetone and isopropanol while K325A was stimulated by ethanol, but inhibited by acetone. Overall, AT2 lipase displayed attractive biochemical properties exclusively as a coldadapted,organic solvent stable enzyme isolated from a mesophilic Staphylococcus epidermidis AT2. The functional properties of the enzyme in correlation to its structural architecture were investigated through homology modeling and structural modification. This enzyme was also identified to be recalcitrant to crystallization in its native form due to its inherent flexibility and molecular surface property. Nonetheless, AT2 lipase shows a huge potential to be employed in various industrial applications.